Harnessing administrative data for humanitarian responses - Carter, Karen; Alley, Kate; Han, Hye Jung (International Journal of Population Data Science, 2019)
The need to improve data to support effective responses in humanitarian settings and emergencies is widely recognized; and there is a growing understanding that administrative data systems can be an important source of data in these contexts. Government data systems however are often overlooked, particularly in developing countries, due to access or quality concerns. New systems are frequently established to respond to humanitarian data needs – particularly in protracted emergency settings. This may be necessary in some circumstances due to a collapse or absence of existing systems, but often duplicates government information structures. In the long term, parallel systems risk undermining national systems which may take a significant time to recover or re-build, and can divert highly limited resources. Routine government administrative data systems need to be both more responsive to changes in the environments and communities in which they are operating, and resilient enough to remain operational and secure in those changed circumstances. This work aims to explore what this means in system design, operation, governance, and preparedness for key sectors; to provide practical guidance for national governments and supporting agencies. Findings will be drawn from literature review, expert opinion, and field examples. Case studies will be undertaken in two countries that are either considered “fragile” or have recently responded to an emergency. Work will focus on areas in which UNICEF has a formal role, however it is anticipated to highlight issues relevant to a broad spectrum of humanitarian data needs. Preliminary findings are anticipated to be published towards the end of 2019; and will compliment work programs on developing an understanding of administrative data maturity, and the global standards and norms for upholding the rights of children affected by humanitarian crises, such as UNICEF's Core Commitments for Children in Humanitarian Action.